Various bioactive peptides in collagen hydrolysate from salmo salar skin and the combined inhibitory effects on atherosclerosis in vitro and in vivo. (July 2022) - Liu, Hui; Yang, Yijie; Liu, Yibo; Cui, Liyuan; Fu, Lulu; Li, Bo
Graphical abstract: Highlights: Multifunctional peptides FAGPPGGDGQPGAK and IAGPAGPRGPSGPA were identified from salmo salar skin collagen hydrolysate (SCH). SCH protected endothelial cell injury and regulated inflammation, oxidative stress as well as platelet aggregation in vitro and in vivo . SCH inhibited aortic intima thickening and lipid plaques formation in ApoE -/- mice, which was better than that of aspirin in the early progression of atherosclerosis and exhibited a comparable effect with aspirin in the mid-stage progression. SCH was a potential dietary supplement for the primary prevention of AS. Abstract: Atherosclerosis (AS) is the underlying condition in most cardiovascular diseases, which is blood vessel inflammation participated by many factors. Collagen hydrolysate from salmo salar skin (SCH) obtained in this study showed strong anti-inflammatory activity, protection of endothelial cell injury, antioxidant activity, and anti-platelet aggregation activity in vitro, exhibiting a great potential of attenuating AS. In this study, multifunctional peptides FAGPPGGDGQPGAK and IAGPAGPRGPSGPA, which mainly showed strong anti-inflammatory activity, were identified from SCH after separation of ultrafiltration and column chromatography. Moreover, SCH (contained anti-platelet peptides and anti-inflammatory peptides) was observed to inhibit arterial intima thickening and plaques formation in apolipoprotein E-deficient (ApoE -/- ) mice fed with high-fat diets without side effects, exhibiting a comparable effect with aspirin. SCH showed combined effect on regulating serum biomarkers of inflammation (IL-6 and TNF-α), endothelial injury (MCP-1), platelet activation (TXB2 and PF4) and oxidative stress (MDA and CAT). This research suggested SCH as a potential dietary supplement for the primary prevention of AS.